THE SELECTION OF NATIVE KAZAKHSTAN STRAINS ENTOMOPATHOGENIC MICROORGANISMS TO CREATE BIOLOGICS (Experimental biology, 2016)
Ecosystemly using of pesticides leads to the gathering of the chemicals with big toxies in the growers, in the grounds and in the water leading to the unbuild biocenose. A big gathering of concer thigs call allergic reactions.In nowadays in the deference of the growers from the pestes and illnesses all the big actuality acquires biological method of the force, which root are microorganisms with express biological activity sparch and selection such bio objects for making further home preparations are the aims of there works.In the work data will of learning biological activating toxin with the entomopathogenic of learning morphocultural especially and learning biological activity toxin local entomopathogen strains for the ferce with the wrecker of the culture. Were learned biochemical feature in every sphere also were given date of learning biological activity. In the matter for trices. Got results permitted select father search 4 presspective trains emtomopathogenic bacteria.
Keywords: the inoculant strain; the insecticidal crystals; soil